Monophasic demyelination reduces brain growth in children. (2nd May 2017) - Aubert-Broche, Bérengère; Weier, Katrin; Longoni, Giulia; Fonov, Vladimir S.; Bar-Or, Amit; Marrie, Ruth Ann; Yeh, E. Ann; Narayanan, Sridar; Arnold, Douglas L.; Verhey, Leonard H.; Banwell, Brenda; Collins, D. Louis
Abstract : Objective: To investigate how monophasic acquired demyelinating syndromes (ADS) affect age-expected brain growth over time. Methods: We analyzed 83 pediatric patients imaged serially from initial demyelinating attack: 18 with acute disseminated encephalomyelitis (ADEM) and 65 with other monophasic ADS presentations (monoADS). We further subdivided the monoADS group by the presence (n = 33; monoADSlesion) or absence (n = 32; monoADSnolesion) of T2 lesions involving the brain at onset. We used normative data to compare brain volumes and calculate age- and sex-specific z scores, and used mixed-effect models to investigate their relationship with time from demyelinating illness. Results: Children with monophasic demyelination (ADEM, non-ADEM with brain lesions, and those without brain involvement) demonstrated reduced age-expected brain growth on serial images, driven by reduced age-expected white matter growth. Cortical gray matter volumes were not reduced at onset but demonstrated reduced age-expected growth afterwards in all groups. Brain volumes differed from age- and sex-expected values to the greatest extent in children with ADEM. All patient groups failed to recover age-expected brain growth trajectories. Conclusions: Brain volume, and more importantly age-expected brain growth, is negatively affected by acquired demyelination, even in the absence of chronicity, implicating factors other than active inflammation as operative in this process.